PENANGANAN PIDANA PENGANIAYAAN MELALUI PENDEKATAN RESTORATIF JUSTICE - Karsa Sitorus, Ruari Prasetia; Kurniati , Yeti (Wacana Paramarta: Jurnal Ilmu Hukum, 2024)
In this article, we will see how restorative justice methods are applied in criminal investigations in Indonesia. This study shows that the conventional criminal justice system is ineffective because it concentrates on punishing criminals. Victims' needs are considered, and material justice is guaranteed. Second, a focus on social relationships and social improvement is the basis of a restorative approach. Crime undermines social justice. Perpetrators, victims, their families, and other stakeholders who simply want symptom management and recovery are involved in this approach. In addition, the restoration of a fair situation in the system was discussed at the beginning of the article. Because it is not regulated by specific laws relating to the perpetrators, criminal justice in Indonesia is still very limited. However, restorative justice offers a broader alternative that focuses on the following: recovery of victims and communities; victim involvement in the trial; direct responsibility of the perpetrator; and community involvement.